A republican plated denarius from Aquincum - Juhász, Lajos (Dissertationes Archaeologicae, 2019)
A puzzling plated republican denarius was found decades ago in the civil town of Aquincum. Due to its worn state its identification was troublesome, but it turned out to be an imitation of M. Furius’ coin minted in 119 BC. It is unique for Aquincum, and also quite rare in Pannonia, which raises a number of questions. Even more perplexing are the two mountings on the obverse, which served to fasten the coin to some other object. It is unfortunately impossible to tell, when and why this 2nd century BC plated denarius appeared in the 2–3rd centuries AD civil town.